2015
DOI: 10.1111/iju.12680
|View full text |Cite
|
Sign up to set email alerts
|

Non‐inferiority of silodosin 4 mg once daily to twice daily for storage symptoms score evaluated by the International Prostate Symptom Score in Japanese patients with benign prostatic hyperplasia: A multicenter, randomized, parallel‐group study

Abstract: Abbreviations & AcronymsObjectives: To compare the effect of treatment with silodosin 4 mg once daily versus that of silodosin 4 mg twice daily on storage symptoms in Japanese patients with benign prostatic hyperplasia. Methods: A prospective, multicenter, 12-week, open-labeled study randomized a total of 268 men aged 50 years or older with benign prostatic hyperplasia and overactive bladder to silodosin 4 mg/day or 8 mg/day. Changes in the end-points of the average value of International Prostate Symptom Scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
2
13
0
1
Order By: Relevance
“…Third, the incidence of AEs including ejaculation disorders and low blood pressure will be minimized with the lower dose of silodosin, because AEs are usually dose‐dependent. In a recent study, the AE rate was lower in patients receiving half‐dose (4 mg) silodosin than in those receiving full‐dose (8 mg) silodosin (11.3% vs. 18.3%) …”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Third, the incidence of AEs including ejaculation disorders and low blood pressure will be minimized with the lower dose of silodosin, because AEs are usually dose‐dependent. In a recent study, the AE rate was lower in patients receiving half‐dose (4 mg) silodosin than in those receiving full‐dose (8 mg) silodosin (11.3% vs. 18.3%) …”
Section: Discussionmentioning
confidence: 92%
“…Wada et al and Matsui et al showed that single half‐dose silodosin was effective in 63–76% of patients with LUTS/BPH . In a recent large randomized study of 268 LUTS/BPH patients, Seki et al demonstrated the non‐inferiority of single half‐dose silodosin to full‐dose silodosin . Single half‐dose silodosin has several potential merits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous meta-analysis and sympathetic reviews have been conducted but the grouping method is not detailed due to a limited number of articles [14][15][16][17] . To date, more and more researches have evaluated the difference of efficacy and safety among silodosin and other medications whereas the results are controversial [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] .Therefore, we decided to perform this meta-analysis through a more detailed systematic review of those accessible RCTs to distinguish silodosin's superiority and non-inferiority to placebo and other medications in males with LUTS/BPH, which can provided more dependable guidance for the clinical application of silodosin.…”
Section: Introductionmentioning
confidence: 99%